Ultrafast Domain Wall Propagation Due to the Interfacial Dzyaloshinskii-Moriya Interaction - Mancilla-Almonacid, D (Institute of Physics Publishing, 2020)
It is shown that the interplay between curvature and interfacial Dzyalonshinsky-Moriya interaction (DMI) is a pathway to ultrafast domain wall (DW) dynamics in ferromagnetic nanotubes. In this work, we theoretically study the effect that interfacial DMI has on the average velocity of a vortex DW in thin ferromagnetic nanotubes grown around a core composed of heavy atoms. Our main result shows that by delaying the Walker breakdown instability, the DW average velocity is of the order of 103 m s-1, which is greater than usual values for these systems. The remarkable velocities achieved through this configuration could greatly benefit the development of spintronic devices. © 2020 IOP Publishing Ltd.